New modalities for managing drought risk in rainfed agriculture: Evidence from a discrete choice experiment in Odisha, India - Ward, Patrick S.; Makhija, Simrin (International Food Policy Research Institute, 2016)
In this paper we explore the potential for a new approach to managing drought risk among rainfed rice producers in Odisha, India. Droughts have historically been a serious constraint to agricultural production in rainfed agricultural systems, with droughts resulting in significant reductions in both yields and cultivated area, in turn leading to significant impacts on rural livelihoods and food security. Scientists and policy makers have proposed various strategies for managing risks, with limited success. In this study we consider two such strategies, specifically drought-tolerant rice and weather index insurance. While neither drought-tolerant cultivars nor weather index insurance products are perfect solutions for adequately managing drought risk in and of themselves, there is scope to exploit the benefits of each and bundle them into a complementary risk management product, specifically through proper index calibration and an optimized insurance design. In this study, we explore preferences for such a complementary risk management product using discrete choice experiments in Odisha, India. We are able to estimate the added value that farmers perceive in the bundled product above and beyond the value associated with each of the independent products. We also show that valuations are sensitive to the basis risk implied by the insurance product, with farmers less enthusiastic about risk management products that leave significant risks uninsured.